Theoretical and methodological foundations of the formation and implementation of strategies for investment development of the region - Goyko, А. F. (Ways to Improve Construction Efficiency, 2018)
The theoretical and methodological foundations of the study of investment development of the regional economy are systematized. The current modern structural and logical scheme for the development and implementation of the region’s investment development strategy. The concepts of "investment activity", "investment development of the region", "investment potential of the region" are defined. The modern structural and logical scheme of development and realization of the strategy of investment development of the region has been formed, the factors of investment development of the region's economy have been systematized, the role of the state in it has been determined, the key elements of the formation of the regional investment strategy have been identified, the structural and logical scheme of the formation of the regional investment strategy has been created